2012
DOI: 10.1093/ndtplus/sfr167
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium and outcomes in patients with chronic kidney disease: focus on vascular calcification, atherosclerosis and survival

Abstract: Patients with chronic kidney disease (CKD) have a high prevalence of vascular calcification, and cardiovascular disease is the leading cause of death in this population. However, the molecular mechanisms of vascular calcification, which are multifactorial, cell-mediated and dynamic, are not yet fully understood. We need to address ways to improve outcomes in CKD patients, both in terms of vascular calcification and cardiovascular morbidity and mortality—and to these ends, we investigate the role of magnesium. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(90 citation statements)
references
References 74 publications
1
89
0
Order By: Relevance
“…Treatment with vitamin D compounds could reverse these changes (7). Similarly, clinical studies demonstrated that Mg therapy significantly suppressed PTH secretion in CKD, which in turn prevented the development of uremic bone diseases and AC (41,62). Moreover, low BMI was associated with increased AC, possibly through calcium mobilization from bone, resulting in decreased bone mineral density (10).…”
Section: The Possible Mechanisms For Mics-induced Ac In Ckdmentioning
confidence: 99%
“…Treatment with vitamin D compounds could reverse these changes (7). Similarly, clinical studies demonstrated that Mg therapy significantly suppressed PTH secretion in CKD, which in turn prevented the development of uremic bone diseases and AC (41,62). Moreover, low BMI was associated with increased AC, possibly through calcium mobilization from bone, resulting in decreased bone mineral density (10).…”
Section: The Possible Mechanisms For Mics-induced Ac In Ckdmentioning
confidence: 99%
“…Fluoride therefore, is an excellent geochemical carrier and a marker for a large number of possible causative agents. It is noteworthy that with the exception of the pineal gland, it is the kidney which accumulates fluoride most in the human body (Massy and Drüeke, 2012). The fact that the ionic radius of the fluoride ion (0.133 nm) is very similar to that of the hydroxyl ion (~0.110 nm), makes fluoride an excellent aquaphile.…”
Section: Geochemistry Of Groundwater Fluoridementioning
confidence: 99%
“…It was also reported that there was a significant reduction of fluorosis in Mgfed animals presumably due to a decrease in the intestinal absorption of fluoride (Chouhan and Flora, 2008;Khandare et al, 2011). A noteworthy observation is that patients with CKD have a high prevalence of vascular calcification and cardiovascular disease is the leading cause of death in CKD populations (Massy and Drüeke, 2012). Observational studies had shown that low serum Mg may be an independent risk factor for premature death in CKD patients and patients with mildly elevated serum levels could have a better chance of survival over those with lower Mg levels.…”
mentioning
confidence: 99%
“…In the most severe cases, these are usually associated with hypokalaemia and hypocalcaemia [31][32][33][34]. Outcome studies in the general population have indicated potential associations between low serum Mg levels and atherosclerosis, hypertension, diabetes, and left ventricular hypertrophy, as well as both CVD mortality and allcause mortality [13,[35][36][37]. In several studies, higher mortality rates were also observed in maintenance HD patients with low serum Mg levels [38][39][40].…”
Section: Mg and Outcome In Ckd And Esrdmentioning
confidence: 99%
“…There are several mechanisms that may explain the increased CVD risk of patients with hypomagnesaemia [37]. Mg possesses an anti-atherosclerotic effect, which is mediated partly via its anti-inflammatory and antioxidant properties; conversely, by inhibiting endothelial proliferation, upregulating plasminogen activator inhibitor-1 and vascular cell adhesion molecule-1, Mg deficiency promotes endothelial dysfunction [20,[43][44][45][46].…”
Section: By Which Mechanisms Could Mg Be Protective?mentioning
confidence: 99%